Rectal nonsteroidal anti-inflammatory drugs and pancreatic stents in preventing post-endoscopic retrograde cholangiopancreatography pancreatitis in high-risk patients: A network meta-analysis. Issue 42 (16th October 2020) - Shou-xin, Yin; Shuai, Han; Fan-guo, Kong; Xing-yuan, Dao; Jia-guo, Huang; Tao, Peng; Lin, Qi; Yan-sheng, Shang; Ting-ting, Yang; Jing, Zhao; Fang, Li; Hao-liang, Qi; et al.
Abstract: Background: 100 mg rectal nonsteroidal anti-inflammatory drugs (NSAIDs) and pancreatic stents both significantly reduce the incidence of post-endoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. Direct comparison of randomized controlled trials (RCTs) between them in high-risk patients is absent. We conducted this network meta-analysis to indirectly compare the efficacies of 100 mg rectal NSAIDs and pancreatic stents in preventing post-ERCP pancreatitis (PEP) in high-risk patients and help us decide which is preferred in clinical practice. Methods: A comprehensive search was done to identify RCTs published in English full-text. Interventions included 100 mg rectal NSAIDs (diclofenac or indomethacin) and pancreatic stents. Only studies with high-risk patients of PEP were included. Meta-analyses of NSAIDs and pancreatic stents were conducted respectively. A network meta-analysis using the Bayesian method was performed. Results: We included 14 RCTs, 8 on pancreatic stents and 6 on 100 mg rectal NSAIDs in high-risk patients. There was no direct comparison between them. After excluding an outlier study on NSAIDs (n = 144), meta-analyses showed they both significantly and statistically reduced the incidence of PEP in high-risk patients (pancreatic stents: n = 8 studies, random-effects risk ratio (RR)0.41, 95%CI 0.30–0.56, I 2  = 0%; NSAIDs: n = 5 studies, random-effects RR 0.37, 95%CI 0.25–0.54, I 2  = 0%). And network meta-analysis showed efficacy of 100 mg rectal NSAIDs was equal to pancreatic stents (random-effects RR 0.94, 95%CI 0.50–1.8). Conclusions: The efficacy of 100 mg rectal NSAIDs (diclofenac or indomethacin) seems equally significant to pancreatic stents in preventing PEP in high-risk patients. Considering the cost-effectiveness and safety, 100 mg diclofenac or indomethacin may be preferred.